Answer:
<h3>B. 8</h3>
Step-by-step explanation:
Simplifying
28 + 12x = 8x + -4
Reorder the terms:
28 + 12x = -4 + 8x
Solving
28 + 12x = -4 + 8x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-8x' to each side of the equation.
28 + 12x + -8x = -4 + 8x + -8x
Combine like terms: 12x + -8x = 4x
28 + 4x = -4 + 8x + -8x
Combine like terms: 8x + -8x = 0
28 + 4x = -4 + 0
28 + 4x = -4
Add '-28' to each side of the equation.
28 + -28 + 4x = -4 + -28
Combine like terms: 28 + -28 = 0
0 + 4x = -4 + -28
4x = -4 + -28
Combine like terms: -4 + -28 = -32
4x = -32
Divide each side by '4'.
x = -8
Simplifying
x = -8